Is the United States Stock Market Getting Riskier? - SUAREZ, Ronny (Journal of Advanced Studies in Finance; Vol 8 No 1 (2017): JASF Volume VIII Issue 1(15) Summer 2017, 2017)
In this paper, we compared the distribution of the S&P 500 Index monthly returns of the period 1957-1986 against the period 1987-2016 to evaluate the presence of extreme events. The last 30 years have recorded a higher (lower) probability to exceed a given negative (positive) monthly return compare with the probability of exceedance of the three previous decades.